Examining the impact of organizational creativity and organizational innovation on organizational performance in the UAE Ministry of Interior: the mediating role of financial governance - Alhammadi, Mariam Mohammed Hassan (2024)
Financial governance was essential in any organization's operation that adhere to a responsible and sustainable manner. It ensures adherence to regulations and laws in order to prevent organizations from severe consequences such as fines, lawsuits, and reputational damage. The Ministry of Interior in the United Arab Emirates (UAE) has experienced a transformative shift by transitioning from a reactive police force to proactive law enforcement and seeking to prevent crime before it occurs. To implement new policies and optimize performance, the Ministry widely applies financial governance principles, namely participation, evaluation, effectiveness, transparency, justice, equality, and responsibility. These principles were said to contribute significantly towards performance improvements. Hence, the objectives of this study were to examine the effects of organizational creativity and innovation towards the Ministry's performance and analyzing the indirect effects of financial governance on these relationships. The research collected the data from 356 UAE officers in the Ministry of Interior through a cross-sectional approach using a self-administered questionnaire. Analysis result from the Partial Least Square-Structural Equation Modelling (PLS-SEM) revealed a significant effect of organizational creativity on the performance of Ministry of Interior, UAE. The direct effect of organizational innovation on the Ministry’s performance also remained significant. Also, financial governance partially mediated the relationships between organizational creativity, innovation, and performance. Theoretically, this study contributed to the use of Componential Theory of Organizational Creativity and the Financial Governance Theory in studying the context of organizational creativity, organizational innovation and financial governance in enhancing the performance of UAE Ministry of Interior. From a practical point of view, this study found that promoting a culture of creativity, adopting innovation, and ensuring robust financial governance are important strategies for acquiring excellence in performance within the Ministry.